2014
DOI: 10.1007/s12070-014-0726-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and Computed Tomographic Evaluation of Influence of Nasal Septal Deviation on Lateral Wall of Nose and Its Relation to Sinus Diseases

Abstract: To correlate symptoms of deviated nasal septum (DNS) and chronic rhinosinusitis with the findings of nasal endoscopy and computed tomographic (CT) imaging. To evaluate the influence of degree of septal angle deviation on the severity of lateral nasal wall abnormalities. A prospective study was conducted on 67 patients with clinical evidence of DNS and chronic sinusitis attending ENT OPD between January 2012 and September 2013. All these patients underwent nasal endoscopy and CT scan PNS coronal sections. Direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 13 publications
4
33
0
5
Order By: Relevance
“…The dynamic theories attributed the sinusitis to the impairment of the mucociliary function of the nasal mucosa and the affection of airflow by the DNS causing mucosal mucosal dryness and the pressure of air flow changes within the sinuses. [12][13][14] Many studies have been conducted to evaluate the reality of such correlation between sinusitis and DNS. Moorthy et al found that the DNS can be associated with significant sinonasal disease even in absence of any nasal symptoms, especially an "S" shaped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic theories attributed the sinusitis to the impairment of the mucociliary function of the nasal mucosa and the affection of airflow by the DNS causing mucosal mucosal dryness and the pressure of air flow changes within the sinuses. [12][13][14] Many studies have been conducted to evaluate the reality of such correlation between sinusitis and DNS. Moorthy et al found that the DNS can be associated with significant sinonasal disease even in absence of any nasal symptoms, especially an "S" shaped.…”
Section: Discussionmentioning
confidence: 99%
“…8 Poorey et al reemphasized the concept that septal deviation causes obstruction at OMC which results in an increased incidence and severity of bilateral chronic sinus disease. 13 But the problem in this two studies is the randomization of the samples, as all the samples are patients with DNS, but either symptomatic or not. Ozkurt et al who studied a well randomized sample of larger group of cases and concluded that the presence of DNS creates a risk factor for chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that patients with RCMs had a higher Lund-Mackay radiological score for chronic rhinosinusitis than patients without cysts (2,12). It is generally believed that OMCO, accessory ostia, AMT, and NSD can lead to complaints or symptoms via chronic paranasal sinus inflammation (13)(14)(15)(16). Therefore, recurrent mucosal inflammation is a putative risk factor for the development of RCMs.…”
Section: Discussionmentioning
confidence: 99%
“…Concha bullosa, paradoxical concha, bifid concha, and NSD are common anatomical variants occurring in as much as 30%-70% of the population (15,23). The middle turbinate is important in the drainage of the maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been done in different geographic areas have shown a varying pattern of symptoms of sinusitis [9]. A thorough literature search revealed that there are minimal studies done in this region, hence we considered it worthwhile to study the clinic therapeutic profile of patients with sinusitis and to find out the correlation of clinical profile with treatment.…”
Section: Introductionmentioning
confidence: 99%